(untitled) (CIPEEX, 2025)
This project is designed to support individuals at various stages of their fitness journey, from beginners to more advanced gym-goers, by providing a personalized approach to health and fitness. Users will input their personal information, including height, weight, age, and other relevant data, into the application. They will also specify how many days per week they are available for training, as well as their specific fitness goals, whether they want to lose weight, gain muscle, or maintain their current physique. Based on this information, beginners will receive tailored workout routines and diet plans that match their goals and fitness level.The application will include a comprehensive frequently asked questions (FAQ) section, as well as a detailed guide that explains the reasoning behind the recommended caloric intake and the concept of calories (kcal). The results of using the app will largely depend on the commitment of each individual. The platform will send personalized notifications to encourage users to stay consistent, similar to how Duolingo motivates users with its mascot. This app seeks to help users develop a more active lifestyle, encouraging long-term consistency and promoting the achievement of fitness goals.